Project SAMPHIRE: Crowd Sourcing Maritime Archaeology data off Scotland's West Coast. (3rd April 2019) - McCarthy, John; Benjamin, Jonathan
ABSTRACT: Perhaps the greatest barrier to effective management of underwater cultural heritage is the lack of data on the nature and location of offshore archaeological resources. This is a problem shared with terrestrial archaeology, but is particularly acute due to the limitations of survey techniques in the underwater environment. In Scotland <15% of known ship losses from the last 200 years have been located and the record is far less comprehensive for earlier periods, verging on a near total data gap. Most known archaeological sites in Scottish waters have been discovered through large-scale sonar survey of relatively low resolution and a considerable bias has been introduced in the archaeological record; this has favored the discovery and documentation of larger and more recent, often upstanding, metal shipwrecks. This article presents the methods and results from a three-year project designed to reduce this bias by demonstrating large-scale prospecting for maritime archaeology through a community-based crowd-sourcing approach. Project SAMPHIRE (the Scottish Atlantic Maritime Past: Heritage, Investigation, Research and Education Project) was geographically focused on the west coast of the Scottish mainland and was undertaken between 2013 and 2015, resulting in a large number of new archaeological discoveries, including shipwrecks, aircraft, and other material of a much more varied nature than what is typically found through large-scale hydrographic surveys.